Functional multipotency of stem cells: Biological traits gleaned from neural progeny studies. (November 2019) - Teng, Yang D.
Abstract: In this review, a stem cell concept, initially defined by the author more than 10 years ago focusing on neural stem cells, has been systematically refined and updated. Relative to the conventional view which touched principally on the totipotency, pluripotentcy and multipotency of cell lineage differentiation (e.g., the ability of neural stem cells to grow into all three types of neural cells), accumulated data obtained by other researchers and my own team promoted me and my colleagues to propose and establish a new biological concept: Functional Multipotency of Stem Cells . The goal is to recognize the biofunctional multipotency of the stem cell to mediate homeostasis during development and adulthood. Under this academic context, an enriched repertoire of signaling, epigenetic and genetic events has been revealed. Such insight has enabled appreciation of the wide range of molecular tactics the stem cell can use at each developmental or adult stage. The multifunctionality allows stem cells to properly migrate, differentiate, and integrate into as well as prepare, influence, and repair the neighboring cells to steer the micro- and macro-environment towards the formation and self-maintenance of a physiological organ and system. It has been demonstrated that embracing this concept of the stem cell's "functional multipotency" is pivotal for correctly, efficiently, and optimally investigating stem cells to advance fundamental biology and therapeutic translation.